Biomechanical study of olecranon plate fixation in comminuted osteoporotic fracture model: locking compression plates versus dynamic compression plates. Issue 2 (March 2018) - Shakir, Irshad; Israel, Heidi; Cannada, Lisa K.; Bledsoe, Gary
Abstract : This cadaveric biomechanical study compared locking compression plates (LCP) to dynamic compression plates (DCP) in a comminuted olecranon fracture using cyclic loading to measure fragment displacement and maximal failure load. Eight paired human cadavers were used. We confirmed all specimens were osteopenic using DEXA. One paired half of the specimens randomly received LCP fixation and the other DCP. Implants were secured to the intact ulna prior to creating an osteotomy. Two vertical osteotomies were created to simulate a fracture gap of 5 mm. The specimens were loaded and placed on the MTS machine. Saw-toothed cyclic loading was applied and force/gap displacement measured. Failure was defined as fracture gap greater than 2 mm or catastrophic failure of the bone/construct. Biomechanical parameters were compared between two groups. The average force for the DCP was 22.12 N compared to 33.40 N ( P <0.05) for the LCP. The average gap for the DCP was 7.32 mm compared to 6.40 mm ( P <0.05) for the LCP. The force measure was statistically significant at 60, 70, 80, 90, and 100 mm of displacement ( P <0.05) for the LCP. This implies that the LCP was able to withstand higher force than the DCP. The gap displacement was statistically significant at 60, 70, 80, 90, and 100 mm of displacement ( P <0.05). This implies that the LCP maintained the reduction better than the DCP. No differences in force/gap were noted when comparing gender, right versus left forearm, or osteoporotic versus osteopenic bone. There was no difference when failure occurred between the DCP and LCP groups. Our study found that LCP was able to withstand higher force than DCP, and there was less displacement of the fracture with biomechanical testing in the LCP compared to the DCP. Both could be appropriate surgical techniques for fixation of comminuted olecranon fractures. When treating comminuted and osteopenic fractures, LCP are advantageous. Further studies would be needed to compare these two plates clinically.